Analysis of Ion Composition of Ambient PM2.5 During Burning Season in Chiang Mai Province - Patcharee Saejiw (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Chiang Mai Province is located in a basin and therefore experiences an annual increase of air pollutants particularly particulate matters with an aerodynamic less than or equal to 2.5 µm (PM2.5) during the dry season. The main source of air pollution in this area is open burning. This study aims to analyse ion composition of ambient PM2.5 during open burning season for source identification. The PM2.5 samples (24-hour sampling) were collected by using a mini-volume air sampler with a flow rate of 5 L/min during 13 February – 30 April 2018. A sampling station is located in the sub-urban area of Chiang Mai city surrounded by agricultural fields. The samples (n=71) were extracted in deionized water and analysed for their ion composition by ion chromatography. An average PM2.5 concentration was 45.5 ± 25.7 µg/m³, while min – max values were 7.0 – 185 µg/m³ . About 31 % (22 days) of the sampling showed that 24-hour average PM2.5 concentration was higher than Thailand ambient air quality standard (50 µg/m³). Dominant ion species of PM2.5 were sulfate (6.75±3.05µg/m³), ammonium (2.06±1.10 µg/m³) and nitrate ( 2.04±0.67 µg/m³). Potassium ion (biomass burning tracer) was also found (0.42±0.91 µg/m³). PM2.5 mass concentration was well correlated with nitrate and potassium (r~0.7) indicating that they were mainly generated from biomass burning. Sulfate and ammonium were also well correlated (r=0.67) showing the influence of photochemical reactions. The positive correlations revealed various forms of major compounds (i.e.,(NH4) 2SO4 and KNO3). Principal Component Analysis (PCA) of ions identified various sources of PM2.5 in this area including biomass burning, traffic emission, agricultural activity, and soil dust.